Design and Construction of Salapak MSME Kawaluyaan Marketplace, Bandung City - Bakti Bestin; Nanang Ganda Prawira; M. Rivaldi Ardiansyah; Muhammad Agung (Indonesian Scientific Publication, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a vital component of the Indonesian economy. MSMEs have proven to significantly contribute to employment, increase public income, and enhance the country's economic resilience. However, MSMEs still face several obstacles in developing their businesses, particularly in implementing digital technology, online marketing, and ensuring easy access for consumers. Many MSME entrepreneurs in Bandung City still rely on traditional promotional methods such as word of mouth, exhibitions, or distributing brochures, which are less effective in reaching a wider market. This study designs and develops an Android-based marketplace application called Salapak, which serves as a platform for promoting and selling MSME products in Kawaluyaan, Bandung City. The development method used in this study was Agile Extreme Programming, which allowed for a more flexible and faster development process, involving direct collaboration with users. Data collection was conducted through field observations, interviews, documentation, and direct evaluations of MSMEs and relevant agencies. The research results show that the Salapak application has been an effective solution in helping MSMEs expand their marketing reach, increase the visibility of superior products, and make it easier for consumers to find and purchase MSME products digitally. The application also provides automatic notification features, a shopping cart, a product catalog, a product detail page, and an emailed invoice page. For further development, it is recommended to add digital payment integration features, improve the UI/UX, implement delivery tracking, and incorporate an artificial intelligence-based product recommendation system.